ARQ Mechanism in HSDPA - Bestak, Robert (Communications - Scientific letters of the University of Zilina, 2005)
Two principal features of the MAC-hs protocol include retransmissions of erroneous blocks and in-sequence data delivery to the upper layer. The first function is provided through a HARQ mechanism. The second function is achieved with the help of sliding transmission/receiving window and by using a specific numbering. In this paper, the MAC-hs performance for different sliding window sizes, timer values and number of retransmission attempts are investigated. Simulations show that values of these parameters have to be carefully set up in order to prevent incorrect block discards at the receiver side.